2010
DOI: 10.3389/fpsyg.2010.00155
|View full text |Cite
|
Sign up to set email alerts
|

Two Independent Mechanisms for Motion-In-Depth Perception: Evidence from Individual Differences

Abstract: Our forward-facing eyes allow us the advantage of binocular visual information: using the tiny differences between right and left eye views to learn about depth and location in three dimensions. Our visual systems also contain specialized mechanisms to detect motion-in-depth from binocular vision, but the nature of these mechanisms remains controversial. Binocular motion-in-depth perception could theoretically be based on first detecting binocular disparity and then monitoring how it changes over time. The alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 39 publications
4
70
0
Order By: Relevance
“…A study using similar stimuli to display similar cues found that only half of their 62 subjects provided thresholds for use in analysis. 33 The level of stereo-acuity (e.g. STATIC 185@) measured in the study sample may appear poor; this is due to the design of the stimuli used in the experiment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study using similar stimuli to display similar cues found that only half of their 62 subjects provided thresholds for use in analysis. 33 The level of stereo-acuity (e.g. STATIC 185@) measured in the study sample may appear poor; this is due to the design of the stimuli used in the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28] The lowest thresholds were found for the Z-LOCATION CHANGE condition (changing disparity/ fixed pattern), which is consistent with the idea that the CDOT cue alone is not solely responsible for depth detection of motion-in-depth stimuli, but that another cue, the IOVD cue, might be utilised, in line with previous reports. 33 Additional experiments have been conducted to determine whether isolation of the IOVD cue results in the perception of depth. By definition, no disparity information is available in the IOVD cue, as no spatially corresponding points exist between the two eyes; the IOVD cue signals only a change in position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other 16 produced data where we could not be sure that performance was different from chance for either the straightforward (Wilmer, 2008;Hokoda, 1985, Porcar & Martinez-Palomar, 1997, Watanabe et al, 2008, as well as our own lab where we have explored motion in depth (Nefs, O'Hare & Harris, 2010). Many studies do not report in detail how their observers were chosen, nor how many were excluded.…”
Section: Poor Performance For Many Observersmentioning
confidence: 99%
“…In a previous study, we tested a large number (62) of observers on a series of motion in depth tasks and a control dot-density task (Nefs et al, 2010). The idea of this latter task was to test 23 whether some of our naïve observers were poorly motivated.…”
Section: Poor Performance For Many Observersmentioning
confidence: 99%